The Audit (or Iceland, a modern myth) ... - Westerside, Andrew; Baynton, Rachel (University of Lincoln, 2024)
The global economy is a mess. The crash has landed, the tides swept out, and its taken our hope with it. Theres less in our pockets and more to be spent. The rich have got richer, the middles squeezed tight, and the poor are being dragged ever downwards.With the true value of money and the human cost of greed firmly in their sights, Proto-type Theater tell the story of how a nation raised their voices in protest and railed against the currents.Using original text, performance, film, music and animation, THE AUDIT is about finding strength, overcoming a world designed to keep us docile, and how collective power can move a mountain even if only a little.THE AUDIT is Proto-types second theatrical work examining contemporary politics, following A Machine theyre Secretly Building, a smartly intelligent hour-long whizz through the world of surveillance (Lyn Gardner, The Guardian). ...